Case Report: A delicate equilibrium of exocrine pancreatic recovery and hepatotoxicity with elexacaftor/tezacaftor/ivacaftor therapy in a pediatric patient with cystic fibrosis - Coughlin, Michael P.; Sankararaman, Senthilkumar; Roesch, Erica A.; Certo, Emily D.; Brej, Benjamin L.; Konstan, Michael W. (Frontiers in Pediatrics, 2024)
This case report presents a comprehensive evaluation of the complex balance of therapeutic benefits and potential risks associated with the cystic fibrosis transmembrane conductance regulator (CFTR) modulator elexacaftor/tezacaftor/ivacaftor (ETI) therapy in managing an eight-year-old male with cystic fibrosis (CF) and exocrine pancreatic insufficiency (EPI). While ETI therapy significantly enhanced exocrine pancreatic function, it led to hepatotoxicity, necessitating therapy discontinuation. Attempts to restart ETI at reduced doses were unsuccessful due to persistent hepatic dysfunction. Reduced ETI dosing frequency, implemented due to hepatic dysfunctions, did not result in substantial therapeutic benefits. Clinical markers showed a resurgence of severe EPI and sustained need for gastrostomy tube feeds, with only modest improvement in hepatic function compared to the period following ETI cessation or during prior use of CFTR modulator therapy with lumacaftor/ivacaftor. This case underscores the importance of personalized therapeutic approaches, biomarker-guided monitoring, and multidisciplinary insights to optimize CF management while also highlighting the ongoing need for research to mitigate hepatotoxicity risks and ensure long-term therapeutic efficacy.